Spawning, Larval Rearing and Early Growth of Hippopus Hippopus (Linn.) (Bivalvia: Tridacnidae) - Alcala, Angel C.; Solis, E.P.; Alcazar, Sally (Silliman Journal, 2024)
The results of rearing laboratory-spawned eggs and larvae of the giant clam Hippopus hippopus (Linn.) in the laboratory are described. Veliger larvae reared at stocking densities of 1.2 to 5/ml and fed with the unicellular algae Isochrysis galbana and Tetraselmis sp. developed into 3-4-month-old juveniles. The survival rates of 3-4-month-old juveniles from veligers ranged from 0.03 to 2.13%. For successful mariculture, larval mortality rates must be reduced.